Exploring Challenges and Strategies for Online Classroom Interaction - Entusiastik, Entusiastik (Universitas Galuh, 2024)
Research has indicated the importance of classroom interaction as one of the determinant factors for language learning to be successful. However, with the fact that the online learning mode has been a new norm in the education context, creating a supportive classroom interaction is considered challenging. Both the teachers and students rely on the technological resources to interact both synchronously or asynchronously. Although theoretically, the online platforms are available to make interaction more explicit, it seems that interaction among learners during online class is either more difficult to create or is not fully encouraged. This research intends to answer two questions, firstly, what challenges students face which potentially prevent them from participating in classroom interaction? And secondly, what can be done to improve the quantity and quality of classroom interaction to maximize learning. An online survey is conducted to explore possible challenges in creating interactive learning activities as well as strategies to improve classroom interaction. It is expected that the research may offer insights for instructors and educators to have a more meaningful classroom interaction and engage learners more effectively.